(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2017)
The present study aimed to assess the effects of a brief behavioral intervention protocol designed for public employees with a diagnosis of chronic pain. Five female public employeesparticipated, aged between 36 and 61 years; three who had been diagnosed with Fibromyalgia, one with Migraine, and one with Neuritis. The intervention was programmed based on a multiple baseline procedure in four phases: 1) Baseline; 2) Module 1 (Psychoeducation); 3) Module 2 (Relaxation); and 4) Module 3 (Coping Strategies). The following assessment instruments were used: Interview Script; Inventory of Stress Symptoms for Adults Lipp (ISSL); Beck Depression and Anxiety Inventories; FAST Scale and WHOQOL-BREF Inventory. Individual records showed a correlation between pain intensity and poor effectiveness at work (r = 0.86, p